Testing Education: A Survey on a Global Scale - Melo, Silvana M.; Moreira, Veronica X. S.; Paschoal, Leo Natan; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
[Background]: The software industry has a high demand for professionals in the software quality area. However, computing students, in general, leave the university with little or no knowledge in software testing. [Aim] Although previous studies have investigated how software testing is covered in universities, they focus on pedagogical approaches, trends, and technologies for improving the educational process, and do not evaluate in-depth the contents explored. This article addresses a worldwide perspective on the way educators both deal with the software testing subject, materials and details covered, support mechanisms and teaching practices applied, and challenges imposed, and evaluate instruments. [Method] A survey with questions was conducted with software testing professors from April to June 2020 towards investigating the way the subject is taught in the classroom. [Results] Most higher education institutions address the fundamental software testing techniques and criteria, with more completeness in specific than general software engineering courses. Additional findings and discussions are presented in detail throughout the paper. [Conclusion] This study provides a comprehensive overview of the software testing education field from educators' perspectives. We strongly believe it is useful for the understanding of the actual scenario of the topic, provides foundations and directions to new research, guides educators into subjects' conduction and identification of potential weaknesses and solutions to recurrent problems.